Fiddlin' family set for how at Shuler (Raton, NM Raton Range, 1994)
Article is about the Booher Family coming to do a show at the Shuler Theater
Newspaper article
Master list item #: 49
File location is in the Raton file Cabinet
Keywords: Booher Family -- Performance group; Bill Fegan Attractions; Live Performance; Fiddling Performance; Yodeling Performance; Clogging Performance; Shuler Theater; Raton, New Mexico